Analysis of chlorophyll content and its correlation with yield attributing traits on early varieties of maize (Zea mays L.) - Ghimire, Bikal; Timsina, Deepika; Nepal, Jyotsna (Journal of Maize Research and Development, 2015)
Chlorophyll has direct roles on photosynthesis and hence closely relates to capacity for photosynthesis, development and yield of crops. With object to explore the roles of chlorophyll content and its relation with other yield attributing traits a field research was conducted using fourteen early genotypes of maize in RCBD design with three replications. Observations were made for Soil Plant Analysis Development (SPAD) reading, ear weight, number of kernel row/ear, number of kernel/row, five hundred kernel weight and grain yield/hectare and these traits were analyzed using Analysis of Variance (ANOVA) and correlation coefficient analysis. SPAD reading showed a non-significant variation among the genotypes while it revealed significant correlation with no. of kernel/row, grain yield/hectare and highly significant correlation with no. of kernel row/ear and ear weight which are the most yield determinative traits. For the trait grain yield/ha followed by number of kernel row/ear genotype ARUN-1EV has been found comparatively superior to ARUN-2 (standard check). Grain Yield/hectare was highly heritable (>0.6) while no. of kernel / row, SPAD reading, ear weight, number of kernel row/ear were moderately heritable (0.3-0.6). Correlation analysis and ANOVA revealed ARUN-1EV, comparatively superior to ARUN-2 (standard check), had higher SPAD reading than mean SPAD reading with significant correlation with no. of kernel/row, no. of kernel row/ear, ear weight and grain yield/ha which are all yield determinative traits . This showed positive and significant effect of chlorophyll content in grain yield of the maize. Journal of Maize Research and Development (2015) 1(1):134-145 DOI: http://dx.doi.org/10.5281/zenodo.34263